TECHNOLOGIES FOR THE FORMATION OF A HEALTHY LIFESTYLE FOR FUTURE PHYSICAL EDUCATION TEACHERS (Scientific journal of the Fergana State University, 2024)
This article is devoted to the formation of a healthy lifestyle culture among future physical education teachers, the development of physical qualities, the formation of skills of biological, mental, physical condition and work activity, compliance with hygienic rules in education and upbringing.